Pendampingan Perencanaan Pengembangan Desa Wisata Towale Dalam Peningkatan Ekonomi Desa Di Masa Pandemik - Maskuri Sutomo; Muslimin Muslimin; Nudiatulhuda Mangun; Elimawaty Rombe; Edhi Taqwa (Jurnal SOLMA, 2021)
Background: The impact of the Pandemic, which is very pronounced in the tourism sector, requires the government, actors and scholars to be able to adapt and plan tourism development in accordance with current conditions. The tourist village is the possible alternative for tourism; considering that the mobilization of tourists is still local-oriented, the community's involvement in this tour is very high. The government and village communities are required to be able to formulate strategic plans in developing village tourism; given the limited resources they have, the role of academics is needed to assist and facilitate the preparation of projects until they arrive at implementation. Method: This community service approach in the Towale Tourism Village uses a mentoring and facilitation system in planning the development of the Towale Tourism Village. Result: The results of village planning assistance and facilitation focus on increasing tourist attraction and developing village tourism businesses as economic added value for the community. Conclusion: Potential tourist attractions in Towale Village are Karampuana Beach, Traditional Woven Fabric, Auliya Old Mosque, Bulava Pongeo and ontel bike community.